Editors' Introduction - Weiny César Freitas Pinto; Aline Sanches (Critical Hermeneutics)
Present in a significant way in contemporary philosophy, psychoanalysis has become an object of permanent and lively interest for the main philosophical tendencies of the twentieth century. Wherever one looks, from critical theory to phenomenology, from existentialism to structuralism, from hermeneutics to the philosophy of language, from the philosophy of science to the philosophy of mind, it is possible to attest to the existence of a wide and varied philosophical reception of psychoanalysis. Brazilian philosophy is inserted with protagonism in this great framework of interlocution between philosophical discourse and psychoanalytic discourse...